Tetrazolium medium as an aid in the routine diagnosis of Candida - Denny, Maire J. (1968)
The tetrazolium medium described is easily prepared and serves as a rapid, relatively accurate and simple means of differentiating Candida species, particularly C. albicans, from other yeasts. Culture on this medium does not replace other techniques used for yeast identification. No one test alone will suffice and final identification must rest on an overall pattern of characteristics. In the screening of 1,822 yeast isolates in this laboratory, culture on this medium has proved a valuable adjunct to other recognized techniques, and is now in regular use.